Meluruskan Qiyadah Fikriyah (Kepemimpinan Berpikir) Melalui Pendidikan: Sebuah Key Factor Agar Mampu Bersaing di Era Revolusi Industri 4.0 - Buro, Hasan HA (Ta'dibia: Jurnal Ilmiah Pendidikan Agama Islam, 2019)
It is hardly recognized that Islam did not enjoy any power in the Makkah period. No research has been carried out regarding the divine command issued to the Prophet (s) in the letters of Makiyah the first thirteen years of Islam. How historical events have their way of hearing about the way the Prophet has not been explored at all. The fact that this prediction (nubuwat) was made when Muslims were only a handful of helpless people, Islam was expected to be buried in its place, not lacking in miracles. At that point, the assumption that faith will even survive will be considered a pipe dream. But to predict that Islam will not only survive, but grow to develop globally. This paper aims to straighten the qiyadah fikriyah (thinking leadership) through education: a key factor in order to be able to compete in the Industrial Revolution 4.0 era. from the discussion concluded: 1) Written in pages of the date that Islam which was originally only a religion embraced by dozens of people became a great civilization that stood firmly against other civilizations that had existed earlier and until now globalized. 2) Islam spread throughout the world is not an effort made by the Messenger of Allah alone. Because this is not the character of Islamic da'wah that he brings. There are two important stages that are carried out by him, first is the stage of teaching, coaching, preparing thought and anger. Second, is the stage of propagating da'wah and struggle. The first stage succeeded in forming the (group) of their personal friends who had crystallized Islamic thought. The second stage, is the phase of struggle and upheaval of thought. 3) relating to the system in the Industrial Revolution era 4.0, prophesied in the Qur'an: Internet of thing (IoT) (At Takwir [81]: 3). Big Data (At Takwir [81]: 3) digital tracks, fast transportation systems, telephones, satellite systems, and the internet have approached each other to prove the truth of the Koran so that in the Era of Industrial Revolution 4.0, we entered Extra-Terrestrial Life (As. Syuura: [42]: 29). The important thing is the Air Traffic System which in this case is more appropriate if it is categorized as data traffic with digital footprint as the Word of God: (Adz Zaariaat: [51]: 7), (Arrahman, [55] 33). Then the phenomena of behavior of FB (Q.s Al-Ma'arij [70] 19-21) With regard to SMS, Email, WhatsApp Messenger, sending other data (Qs. An Naml, [27]: 40). The Prophet Muhammad advised: "Believers with other believers like a building, mutually reinforcing each other" (Saheeh Muslim), this hadith in the virtual world is known as "viral", which is something that spreads chain. 4) Islam with qiyadah fikriyah (thinking leadership) is the secret. The truth of bisyarah is the truth of revelation which is certainly proven to be true. "This is a promise from Allah Almighty to the Messenger of Allah, that He will make his people (the people of the Prophet Muhammad) as Khulafa 'al-Ardl, namely: human leaders and rulers over them; repaired lands and all humans submit to them.